Adequacy of Anesthesia Guidance for Colonoscopy Procedures - Michał Jan Stasiowski; Małgorzata Starzewska; Ewa Niewiadomska; Seweryn Król; Kaja Marczak; Jakub Żak; Aleksandra Pluta; Jerzy Eszyk; Beniamin Oskar Grabarek; Izabela Szumera; Michał Nycz; Anna Missir; et al. (MDPI AG, 2021)
In patients undergoing colonoscopy procedures (CPs), inadequate dosing of hypnotic drugs (HD) and opioid analgesics (OA) during intravenous sedoanalgesia (ISA) may lead to intraprocedural awareness with recall (IAwR), intraprocedural (IPP) and postprocedural pain (PPP), as well as postoperative nausea and vomiting (PONV). The aim of this study was to evaluate whether the titration of HD and OA based on the observance of changing values of state entropy (SE) and surgical pleth index (SPI) (adequacy of anesthesia-AoA), state entropy alone, or standard practice may reduce the number of adverse events. One hundred and fifty-eight patients were included in the final analysis. The rate of IAwR and IPP was statistically more frequent in patients from the C group in comparison with the AoA and SE groups (p < 0.01 and p < 0.05, respectively). In turn, the rate of PPP, PONV, and patients' and operators' satisfaction with ISA between groups was not statistically significant (p > 0.05). Changes in hemodynamic parameters, demand for HD, and OA were statistically significant, but of no clinical value. In patients undergoing CPs under ISA using propofol and FNT, as compared to standard practice, intraprocedural SE monitoring reduced the rate of IAwR and IPP, with no influence on the rate of PPP, PONV, or patients' and endoscopists' satisfaction. AoA guidance on propofol and FNT titration, as compared to SE monitoring only, did not reduce the occurrence of the aforementioned studied parameters, imposing an unnecessary extra cost.